Occurrence of extended-spectrum beta-lactamases among Escherichia coli isolates from hospitalized and healthy children - Franiczek, R; Sobieszczańska, B; Grabowski, M; Mowszet, K; Pytrus, T (Folia microbiologica, 2003)
The prevalence of extended-spectrum beta-lactamases (ESBL) was determined among isolates of Escherichia coli (n = 63) isolated from hospitalized (43) and healthy (20) children. Ten isolates (21%) were ESBL-positive for two screening tests, the double disk-synergy test and the Oxoid Combination Disk method. One ESBL-positive isolate came from a healthy child. The transfer frequency of oxyimino-beta-lactam resistance from ESBL-producing isolates to E. coli K12 C600 recipient strain ranged from 10(-8) to 10(-5) per donor cell. Donor strains and transconjugants displayed susceptibility patterns typical of ESBL producers. They were resistant to oxyimino-beta-lactams but susceptible to clavulanic acid and carbapenems. Seven out of the 10 ESBL-positive isolates were found to produce MR/MS fimbria, which may play an important role in the colonization of the human intestinal mucosa.
Keywords: Child, Preschool; infekce vyvolané Escherichia coli; beta-Lactam Resistance; hospitalizace; Child; beta-Lactamases; Microbial Sensitivity Tests; dítě; Escherichia coli Infections; střevní sliznice; Escherichia coli; beta-laktamasy; předškolní dítě; beta-laktamy; lidé; beta-laktamová rezistence; Humans; beta-Lactams; Intestinal Mucosa; mikrobiální testy citlivosti; Hospitalization; průjem; Diarrhea